Political and territorial divisions in Silesia 1919-1926 - Kulak, Teresa (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
The article concerns the effects of the Resolution of the Prussian Parliament of 14th October 1919, according to which, before the Plebiscite envisaged in the Treaty of Versailles, the Opole (Oppeln) district (Regierungsbezirk) was separated from the Province of Silesia and given the status of the Province of Upper Silesia, and the Province of Lower Silesia was created from the merged Wrocław (Breslau) and Legnica (Liegnitz) districts. After the Plebiscite, in accordance with the decision of the Council of Ambassadors of 20th October 1921, the Plebiscite area was divided and the portions of the Upper Silesian and Lower Silesian Provinces (from the border region of Wrocław) were assigned to Germany and Poland according to decision made on 10th July 1922. As a result of the Act of the Prussian Parliament of 25th July 1923, two separate Provinces of Upper Silesia and Lower Silesia were established, but the division of the property of the former Province of Silesia between them was decided by the Act of 26th October 1926.
Keywords: Lower Silesia; Upper Silesia; Plebiscite; district; provincial parliament; Prussian Parliament; Regierungsbezirk